Shadows asking an echo to dance' Navigating ambiguity : how former conscripts (1980 - 1990) navigate memories of induction into the SADF and whiteness in the post post-apartheid society - O'Connell, Siona (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2019.